NEUROMUSCULAR MONITORING DURING GENERAL ANESTHESIA: BENEFITS IN REDUCING POSTOPERATIVE COMPLICATIONS - Pedro do Valle Varela, João; Clara Berzoini Albuquerque, Ana; Sandoval Pickert, Fabio; Rezende, Danielle; Bandeira Lima, Julia; Oliveira Gil de Almeida, Yasmin; Lucindo Lakatos, Luiza; Carrara Folly Valente, Jaqueline; Augusto Rocha Pompermayer, Vinicius; Guimarães Cunha, Débora; Pereira Ramos Júnior, Sidney; Wagmacker Barbosa, Bárbara; et al. (Health and Society, 2025)
Neuromuscular monitoring during general anaesthesia is a crucial practice for the proper management of muscle blocks, allowing the dosage of muscle relaxants to be optimized and adverse effects to be minimized. The use of neuromuscular blocking agents is common in surgery, especially to facilitate intubation and muscle relaxation. However, inappropriate or excessive use of these agents can result in post-operative complications, such as residual muscle weakness, breathing difficulties and delayed recovery. Neuromuscular monitoring has proven to be an essential tool for mitigating these risks. The aim of this study is to evaluate the benefits of neuromuscular monitoring during general anesthesia, with a focus on reducing postoperative complications such as residual muscle weakness, respiratory difficulty and prolonged recovery time. The aim is also to compare the results of patients who receive real-time monitoring with those who do not. This is a qualitative literature review whose aim is to explore the implications of neuromuscular monitoring in anesthetic practices and its effects on postoperative recovery, opioid consumption and residual neuromuscular blockade. To this end, the PubMed, Scopus and Web of Science databases will be used. The review will be refined using health descriptors such as “Neuromuscular Monitoring,” “Residual Paralysis,” “Opioid Consumption,” with a time frame from 1998 to 2020, covering both review articles and clinical studies and randomized trials. Neuromuscular monitoring has shown clear benefits in reducing residual muscle weakness and improving postoperative respiratory function. Studies indicate that patients who use real-time monitoring during general anesthesia have shorter recovery times, lower rates of respiratory complications and less need for assisted ventilation. In addition, monitoring allows for more precise dosing of muscle relaxants, avoiding overuse and the occurrence of adverse effects. When applied correctly, monitoring also contributes to reducing the duration of anesthesia and improves the patient’s post-operative experience. Neuromuscular monitoring during general anesthesia is essential for reducing postoperative complications, especially residual muscle weakness and respiratory difficulty. Its effective use contributes to a faster and safer recovery for patients, allowing healthcare professionals to adjust the dosage of muscle blockers more precisely. The widespread implementation of this practice in surgical centers is recommended to optimize anesthetic management and improve postoperative outcomes.